2022
DOI: 10.1039/d2an00358a
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-based autofluorescence imaging to detect bacterial species on laboratory surfaces

Abstract: This work demonstrated instantaneous, reagent- and staining-free, smartphone-based autofluorescence detection of bacterial contamination on typical laboratory desk surfaces. Detection was successfully distinguished from protein, salt, and tap water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…33 Bao et al reported the labeling-free and quantitative evaluation of the growth behavior of microorganisms enclosed in microdevices by autouorescence. [34][35][36][37] However, the method is not suitable for the cultivation of several thousand single cells individually since the method was not equipped with multiply compartmentalized cultivation spaces.…”
Section: Introductionmentioning
confidence: 99%
“…33 Bao et al reported the labeling-free and quantitative evaluation of the growth behavior of microorganisms enclosed in microdevices by autouorescence. [34][35][36][37] However, the method is not suitable for the cultivation of several thousand single cells individually since the method was not equipped with multiply compartmentalized cultivation spaces.…”
Section: Introductionmentioning
confidence: 99%